Problemy ekwiwalencji w międzynarodowych badaniach marketingowych - podejście kulturowe - Karcz, Kornelia (Problems of Equivalence in International Marketing Research - Cultural Approach, 2006)
The article presents the following problems:- kinds of international research versus possibility of their results comparison,- methodological discipline of international marketing research,- cultural conditioning of equivalence in international research,- equivalence of a research object and of a process of direct research - selected problems,- problems of guaranteeing equivalence in international research carried out with the use of Internet.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 59-68